Innate Fear-Induced Weight Regulation in the C57BL/6J Mouse - Genné-Bacon, Elizabeth A.; Trinko, Joseph R.; DiLeone, Ralph J. (Frontiers in Behavioral Neuroscience, 2016)
Regulation of body weight is an important strategy for small prey animals to avoid capture. Field and laboratory studies have shown that prey animals reduce body size when subjected to long-term predator stimuli. However, the causes of predator-induced weight regulation are highly variable and the underlying mechanisms remain unclear. Understanding this phenomenon is important for gaining a better understanding of how animals regulate body weight under ethologically relevant conditions and has implications for obesity. Here we expose inbred C57BL/6J mice to a fear-inducing odorant (2,4,5-trimethylthiazole; mT) to model predation-induced weight regulation. Eight week-old mice were put on a 45% high fat diet or chow diet (5% fat) and exposed daily to mT, an equally aversive dose of butyric acid (BA), or a neutral control scent (almond). mT-exposed mice in both diet groups gained significantly less weight over a 6-week period than BA-exposed mice. This differential weight gain appears unlikely to be due to differences in food intake and activity level, or brown adipose thermogenesis between the mT and BA groups. However, following chronic mT exposure we find increases in ΔFosB protein, a marker for long-term neural plasticity, in the dorsomedial hypothalamus - an area previously implicated in chronic stress and defensive responses, as well as weight regulation. This study establishes a simplified and robust laboratory model of predation-mediated weight regulation with inbred lab mice and fear-inducing odor, and suggests a likely, yet undetermined, metabolic adaptation as contributing to this response.